Tuition fee ; Miss Saigon I ; Dalawang Makata [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Students are up in arms against tuition fee hike and other aspects like socialized tuition, subsidized education in sectarian private schools and other financial assistance which they think will be unfair to them. Shows audition process and recruitment of Filipino talents for a London West End production. A story about a concert featuring two poets and two musicians where Filipino poems are put into music.